Effectiveness of Cutting-Edge Technology for Motel Management System - Perera, Thanushi; Liyanage, Shehan; Ravishan, Hirusha; Kavinda, Thisara; Dulanji Cooray; Dilshan De Silva (International Journal of Engineering and Management Research, 2022)
The online motel management system was designed regarding the client Delicacy Inn, Galle, Sri Lanka. In the present, the client is using a manual system to manage their large amount of data which is having several issues. The proposed system allows users to store and manipulate all the data in the database while making the data handling process in to a very effective manner. The proposed system is developed to cover the process of the motel such as employee management, customer & room management, food & beverages management and transportation management. Human Resource manager is responsible of adding, updating, and deleting employee details. Human Resource manager is able to mark the leave consideration and the salary details of the employees. Human Resource manager can search relevant employee details. Customer Resource manager is responsible of adding, updating, and deleting customer details the customers can register and log in to the system. Customers can order foods, order vehicle for transportation and view bills through their online login. Transportation manager is able to manage the vehicle details and managing the process of that. Food and beverages manager are responsible of managing food items and orders given by the customers. A web application was mainly developed to ensure that the internal procedures in the motel management system are processing well. The system is developed with the intention of reducing data manipulation errors in the current manual process, resulting in considerable development in human resource utilization. The system is designed in a user-friendly manner, with a reliability, in an efficient way and its statistics all the client requirements.